The receptor for advanced glycation end-products (RAGE) and the lung - BUCKLEY, STEPHEN; EHRHARDT, CARSTEN (My University, 2010)
The receptor for advanced glycation end products (RAGE) is a member of the immunoglobulin superfamily of cell surface molecules. As a pattern-recognition receptor capable of binding a diverse range of ligands, it is typically expressed at low levels under normal physiological conditions in the majority of tissues. In contrast, the lung exhibits high basal level expression of RAGE localised primarily in alveolar type I (ATI) cells, suggesting a potentially important role for the receptor in maintaining lung homeostasis. Indeed, disruption of RAGE levels has been implicated in the pathogenesis of a variety of pulmonary disorders including cancer and fibrosis. Furthermore, its soluble isoforms, sRAGE, which act as decoy receptors, have been shown to be a useful marker of ATI cell injury. Whilst RAGE undoubtedly plays an important role in the biology of the lung, it remains unclear as to the exact nature of this contribution under both physiological and pathological conditions.
PUBLISHED
Keywords: BIOMEDICINE; VASCULAR ENDOTHELIAL-CELLS; Cancer